Academic writing: a power game between the generation and accomplishment of ideas - Pinto, Maria da Graça Lisboa Castro (2016)
This text aims at viewing the author of academic writing as a weaver who combines information from different research sources into his/her production in order to achieve the degree of originality expected at this level. This implies dealing with different concepts associated with originality, such as authorship, identity, voice, position, attribution, citation, paraphrase, transgressive intertextuality, plagiarism and patchwriting. Furthermore attention is drawn to the proper use of sources after careful critical reading so that interpretation will replace reproduction and intertextuality will not be transgressive, bearing in mind that patchwriting or even plagiarism may only be tolerated in an early stage of written production. Moreover, students are given intervention cues so as to help them find their own voices as authors, and writing is highlighted as a habit that requires discipline and struggling as well as a craft that implies rigour and commitment.